A Preliminary Study on Auditors’ Performance Attributes – Perceptions from Accounting Firm Practitioners - Louis, Ramesh Ruben; Sulaiman, Noor Adwa; Zakaria, Zarina (Asian Journal of Accounting Perspectives, 2022)
Research aim: Recent occurrences of accounting failures have raised concerns over the quality of auditors’ performance. While there have been numerous studies on audit quality, there are limited research on what attributes constitute proper auditors’ performance. Thus, the objective of this study is to examine auditors’ performance attributes perceived to be important to achieve audit quality by auditors in practice. Design/ Methodology/ Approach: Data were obtained from 307 survey questionnaires received from auditors of large firms, small and medium-sized firms, and sole proprietors. Research finding: The study respondents perceived auditors’ performance related to competencies to perform the audit effectively and performing the audit in accordance with standards and regulations as the most significant attributes. These two key attributes were significant regardless of the types of audits performed (i.e. PLC or SME) and the position of the auditor (management or staff levels). On the other hand, attribute relating to providing individualised attention to clients was perceived to be of the lowest importance to the respondents. Theoretical contribution/ Originality: This study examined various behavioural and individual attributes for proper auditors’ performance, which enhances the literature on audit quality. Practitioner/ Policy implication: Key attributes and behaviours for auditors’ performance can be used by researchers and audit practitioners to set their performance benchmark and also used to assess any shortcomings. Research limitation: The respondents were mainly auditors of small and medium-sized firms and sole proprietors. Keywords: Auditor’ Performance, Attributes, Perceptions, Practitioners Type of article: Research paper. JEL Classification: M42